2021
DOI: 10.12928/dpphj.v15i2.4034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Implementation of the Youth Care Health Service Program in the West Lingkar Health Center of Bengkulu City

Abstract: Background: One of the strategies to overcome adolescent problems is the formation of the Youth Care Health Service Program or Pelayanan Kesehatan Peduli Remaja (PKPR). PKPR itself is a health service program aimed at adolescents and is a forum for overcoming adolescent problems. This study aimed to analyze the implementation of the PKPR program in the working area of the West Lingkar Health Center. Method:  This research was a qualitative descriptive study conducted in March-April 2021. The methods used were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“… 40 Qualitative assessments of PKPR implementation suggested that lack of facilities (e.g., separated room to provide counselling/health services to youth), staffing shortage and/or insufficient training for staff have limited the reach of PKPR, particularly among adolescents who do not attend school. 41 Our data emphasise the need for strengthening school-based and community-based health programs to better orient them towards adolescents.…”
Section: Discussionmentioning
confidence: 83%
“… 40 Qualitative assessments of PKPR implementation suggested that lack of facilities (e.g., separated room to provide counselling/health services to youth), staffing shortage and/or insufficient training for staff have limited the reach of PKPR, particularly among adolescents who do not attend school. 41 Our data emphasise the need for strengthening school-based and community-based health programs to better orient them towards adolescents.…”
Section: Discussionmentioning
confidence: 83%